The Level of Environmental Literacy toward Vocational High School Students in West Java Province - Maknun, Johar; Barliana, Mokhammad Syaom; Cahyani, Diah (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2016)
Environmental literacy as individual knowledge and understanding of aspects of the build environment, the principles that occur in the environment, and is able to act in maintaining environmental quality which is applied in everyday life. Changes in the environment each year will occur both in local and global contexts, so the goal of increased environmental literacy is to prepare people who understand and can cope with environmental issues, so it can be prepared reformer environmental agents that have a positive attitude and action on the environment. The purpose of this research is to gain an environmental profile literacy levels of students Vocational High School (SMK) in West Java. To achieve these objectives, the research method used is descriptive research method. The results showed that the knowledge and understanding of vocational students about the environment, including the unfavorable category. This suggests that environmental literacy vocational students are low. Environmental literacy is essential in tackling the environmental problems. This shows that the necessary efforts to improve environmental literacy vocational students. One of the efforts is the learning environment must be integrated on activities intrakulikuler with election materials in line with the skills of vocational students. In the process of learning needs to be done by implementing the learning that adopts konstruksivisme.